2022
DOI: 10.3390/polym14061254
|View full text |Cite
|
Sign up to set email alerts
|

Polylactide-Grafted Metal-Alginate Aerogels

Abstract: Τhis work describes the synthesis of PLA-grafted M-alginate (g-M-alginate; M: Ca2+, Co2+, Ni2+, Cu2+) aerogels. DL-lactide (LA) was attached on the surface of preformed M-alginate beads and was polymerized, using stannous octoate as catalyst and the –OH groups of the alginate backbone as initiators/points of attachment. The material properties of g-M-alginate aerogels were not affected much by grafting, because the linear PLA chains grew on the M-alginate framework like a brush and did not bridge their points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Lee added N -ethyl- and N -2-hydroxyethyl-substituted maleimide-styrene graft-block copolymer to the polylactide 20 , while in our previous work, it was found that the addition of graphite to PLA is a step towards obtaining material that is cheap and suitable for 3D printing of sliding spare parts 21 . In addition, a polylactide-based material with proper additives can help produce fibre-reinforced composite intended for use in agriculture 22 or metal alginate-grafted PLA aerogels (PLA-g-M-alginate; M: Ca 2+ , Co 2+ ,Ni 2+ , Cu 2+ ) 23 . It was previously reported that diatomaceous earth may also be used to reinforce PLA, which is beneficial for both mechanical and thermal properties of such obtained composites 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Lee added N -ethyl- and N -2-hydroxyethyl-substituted maleimide-styrene graft-block copolymer to the polylactide 20 , while in our previous work, it was found that the addition of graphite to PLA is a step towards obtaining material that is cheap and suitable for 3D printing of sliding spare parts 21 . In addition, a polylactide-based material with proper additives can help produce fibre-reinforced composite intended for use in agriculture 22 or metal alginate-grafted PLA aerogels (PLA-g-M-alginate; M: Ca 2+ , Co 2+ ,Ni 2+ , Cu 2+ ) 23 . It was previously reported that diatomaceous earth may also be used to reinforce PLA, which is beneficial for both mechanical and thermal properties of such obtained composites 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal density [g cm −3 ] Reference 1.0 2.02 ± 0.08 [30] 1.0 1.92 ± 0.03 [30] 1.5 1.82 [31] 2.0 2.07 ± 0.02 [30] 2.0 1.934 ± 0.006 [30] 2.0 1.97 ± 0.03 [32] 2.0 1.95 ± 0.02 [32] 3.0 1.89 ± 0.02 [33] 3.0 1.85 [31] 5.0 0.366 [34] 5.0 1.77 [31] 6.0 1.18 ± 0.16 [35] 10.0 1.84 [31] Median value ± IQR a) 1.89 ± 0.13 a) Due to certain scattering of the literature data, the median was calculated as a measure of central tendency and the interquartile range (IQR) is a measure of statistical dispersion.…”
Section: Mass Fraction Of Alginate In Initial Solution [Wt%]mentioning
confidence: 99%